(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
The article describes the role and prospects of using modern phytosociological databases for complex geobotanical researches. Based on the analysis of foreign and national experience in creating such information resources, the need for their development and standardization by forming a national infrastructure for the input, accumulation, and storage of phytosociological data of Ukraine is substantiated. Such infrastructure provides the development and implementation of unified technical protocols and normative-methodical rules of digitalization, compilation, management, and the use of phytosociological data for complex meta-analyses. Within the one software technical protocols should combine a single taxonomic list to enter data about the species composition of phytocoenoses, as well as a unified form of header data to add other information on plant communities. Based on the analysis of the existing floristic lists used by Ukrainian phytosociologists, the need to create a new most complete species list with current taxonomic data, which will be periodically updated, is provided. Such a list should unite all taxa of vascular plants and cryptogams known from the territory of Ukraine, be as complete and correct as possible. A standard metadata structure has been developed to enter information on the vertical and horizontal structure of phytocoenoses, ecological and physical-geographical conditions, sozological value, as well as habitat and syntaxonomic affiliation of each geobotanical relevé. A communication system is proposed to obtain phytosociological information necessary for specific research, as well as possible forms of control over the move and use of information protected by copyright. Forms of access to data, mechanisms for obtaining them, and a list of rules for regulating compliance with copyright and scientific ethics in the use of data in the analysis process have been developed.